Rancang Bangun Aplikasi Penentuan Harga Jual Pada UD Eka - Anggrina, Stefany Ika; Widodo, Arifin Puji; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
UD Eka is a manufacturing company who produces shoes, rubber slippers, and raw materials to produce shoes such as soles and heels. Production activites are conducted based on â€œmade to orderâ€ and â€œmade to stockâ€. Currently, company determines the selling price based on the selling price from competitorâ€™s company. After that, company compares with the result of estimates production costs and non-production costs. Therefore, company canâ€™t determine the selling price independently and appropriately so the company canâ€™t calculate profit expected (mark up). Based on this problem, have made application which can help to determine the selling price use full costingâ€™s method. The method is selected because can help company to determine the selling price and mark up by paying attention non-production costs and return on investment. Based on test results, application which have been built can generate the selling price and mark up for each product by paying attention the calculation of non-production costs and return on investment appropriately. So, the selling price can be used a reference for company to determine the selling price.